Adjuvant chemoradiotherapy does not improve outcomes in patients with fistula-associated anal adenocarcinoma undergoing abdominoperineal resection - Wang, Min; Xiang, Yu; Wang, Yunshan; Zhang, Jiayi; Zhao, Haoran; Wang, Can; Qiao, Lichao; Yang, Bolin (Frontiers in Oncology, 2022)
Objective: Abdominoperineal resection (APR) is currently established as a standard treatment regimen for fistula-associated anal adenocarcinoma (FAAA), however, the efficacy of chemoradiotherapy (CRT) remains unclear. The aim of this study is to evaluate the role of CRT in patients with FAAA treated with APR through single-center experience and literature review. Methods: A retrospective review was performed on patients with FAAA consecutive treated in our institution from 2005 to 2022. In addition, a systematic literature search was performed using PubMed and MEDLINE. All patients with FAAA who received APR in our institution and reported in the literature were included and divided into three categories for statistical analysis: APR alone (APR group), neoadjuvant therapy combined APR (CRT+APR group), and APR combined postoperative therapy (APR+CRT group). Results: Fifteen patients with FAAA were identified from our retrospective charts review. At a median follow-up time of 18 months, the recurrence-free survival rate was 53.3% and the survival rate was 73.3%. Eight patients underwent APR and 6 received postoperative chemotherapy. Among them, one died, one developed recurrence and the remaining six patients were alive with disease free. We found 37 publications describing 62 patients with FAAA treated with APR. Clinical data from these articles were analyzed together with the 8 cases in our institution. The overall survival rates were 94.1%, 70.8%, and 38.5% at 1-, 3-, 5-years respectively. Combining (neo)adjuvant therapy did not appear to improve outcomes in FAAA treated with APR (CRT+APR vs. APR, p=0.977; APR+CRT vs. APR, p=0.351). Lymph node involvement was shown to be significantly associated with poor outcomes by multivariate analysis (p=0.020). Conclusions: For patients with FAAA without lymph node involvement, APR is adequate to control disease and the addition of CRT does not appear to prolong survival.